From Overthinking to Understanding: Outbond as a Strategy to Improve Self-Awareness and Mental Health Literacy - Reni Nurhidayah; Prima Dewi Kusumawati; Joko Sutrisno; Hengky Irawan (Universitas STRADA Indonesia, 2025)
Adolescence is a critical developmental stage in which individuals often experience psychological challenges such as overthinking, stress, and emotional dysregulation. Limited self-awareness and low mental health literacy exacerbate these challenges, contributing to poor decision-making, heightened anxiety, and stigma. Innovative approaches are needed to promote adolescent mental health.This study aimed to examine the effectiveness of the “Outbond from Overthinking to Understanding” program in improving self-awareness and mental health literacy among adolescents.A quasi-experimental design with pre-test and post-test control groups was conducted among 120 students (60 intervention, 60 control) from senior high schools (SMA) and vocational high schools (SMK) in Kediri, Indonesia. Participants were selected using cluster sampling. The intervention group participated in a one-day outbound program consisting of six activity stations, while the control group received a leaflet on adolescent mental health. Self-awareness was measured using the Self-Reflection and Insight Scale (SRIS), and mental health literacy was assessed with the Mental Health Literacy Scale (MHLS). Data were analyzed using paired and independent t-tests.The intervention group showed significant improvements in self-awareness (Mean Difference = +13.4, p < 0.001) and mental health literacy (Mean Difference = +17.7, p < 0.001), while the control group demonstrated no significant changes. Post-test comparisons revealed higher mean scores in the intervention group compared to the control group for both self-awareness (78.6 ± 7.9 vs. 66.3 ± 8.6, p < 0.001) and mental health literacy (80.2 ± 8.1 vs. 65.0 ± 8.7, p < 0.001).The “Outbond from Overthinking to Understanding” program significantly enhanced self-awareness and mental health literacy among adolescents. Outbound-based experiential learning offers a promising, engaging, and practical strategy for promoting adolescent mental health and should be considered as a complementary approach to conventional school-based education.